Schaum's outline of fluid mechanics and hydraulics - Giles, Ranald V. 4 0 16; Liu, Cheng,;Evett, Jack; 5 (New York : McGraw-Hill, 1994)
A study aid on fluid dynamics and hydraulics, providing over six hundred fully-solved practice problems with concise concept explanations and supplementary problems with answers.
Includes index.
Adult;Adult.
Keywords: 2 -- 0; 6; Fluid mechanics.;Fluid mechanics; 20; 2